The Correlation Study Between Perfectionism and Coping Skills Among Muslim Gifted and Talented Students - Aeisyah Lutfiah Zam Zam; Amirah Zainun (Universiti Sains Islam Malaysia, 2024)
E-Proceeding: Insan Junior Researcher International Conference (iJURECON) 2020 Date: 17-18 November 2020 Organized by: Kolej Genius Insan Virtual Conference Page : 295-297